An Insight into Obesity and Overweight Frequency Secondary to Unhealthy Dietary Intake among Housewives in Pakistan - Tayyaba Zia, Tania Naveel, Syma Arshad, Norina Jabeen, Mubarik Ali, Nadeem Roy, Ali H Amin, Bilal Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
The goal of current review was to determine the occurrence of obesity and overweight among housewives consequently of a poor diet. Obesity has been related to diabetes, heart disease and osteoarthritis in the past. It has been estimated that 190 million overweight and obese people worldwide, obesity and overweight constitute a severe risk to human health. As a result, we looked into the impact of certain eating behaviors on weight among Pakistani housewives. We examined the link between the unhealthy dietary intake and their weight. Genetics, Screen time, sedentary lifestyle, eating speed, number of meals consumed on daily, and high-sugar diets were all found to be associated with obesity. Our findings show that increasing the number of meals per day, slowing down the rate of eating, and limiting high-sugar foods could help.